Labeless Immunosensor Assay for Fluoroquinolone Antibiotics Based Upon an AC Impedance Protocol. - Garifallou, Goulielmos-Zois; Tsekenis, Georgios; Davis, Frank; Higson, Seamus P. J.; Millner, Paul A.; Pinacho, Daniel G.; Sanchez-Baeza, Francisco; Marco, M-Pilar; Gibson, Timothy D. (Taylor & Francis, 2007)
This paper describes the construction of a labeless immunosensor for the antibiotic ciprofloxacin and its interrogation using an AC impedance protocol. Commercial screen-printed carbon electrodes were used as the basis for the sensor. Polyaniline was electrodeposited onto the sensors and then utilized to immobilize a biotinylated antibody for ciprofloxacin using classical avidin- biotin interactions. Electrodes containing the antibodies were exposed to solutions of antigen and interrogated using an AC impedance protocol. The faradaic component of the impedance of the electrodes was found to increase with increasing concentration of antigen. Control samples containing a non-specific IgG antibody were also studied and calibration curves obtained by subtraction of the responses for specific and non-specific antibody-based sensors, thereby eliminating the effects of non-specific adsorption of antigen.
Keywords: Fluoroquinolone; ciprofloxacin; AC impedance; immunosensor; polyaniline